Effects of participatory structure of pre-task planning on EFL learners' linguistic performance and alignment in the continuation writing task. (June 2023) - Xie, Yuanhua; Zhu, Danting
Abstract: Despite the fact that much research has been done on pre-task planning (PTP), none has explored its role in the continuation writing task. This study, therefore, attempted to investigate the effects of individual and collaborative planning on EFL learners' written production and linguistic alignment in the continuation task. Sixty-two Chinese college students were recruited and divided into groups of individual and collaborative planning conditions. They carried out the task in the following sequence: individual reading, individual or collaborative planning, and individual continuation writing. Multivariate analysis of variance (MANOVA), keyness analysis and Pearson correlation were conducted on the collected data. The analyses revealed the following findings: (a) individual planning led to more lexical and syntactic complexity, and slightly more fluency than collaborative planning; (b) both planning conditions yielded similar alignment effects with differential alignments in words, phrases and sentences; and (c) in both planning conditions lexical and syntactic complexity and alignment were negatively correlated with statistical significance, but only in collaborative planning condition coordination was positively correlated with partial alignment. These findings suggest that individual planning can be more advantageous to learners' linguistic performance than collaborative planning in a cognitively simple continuation task. Implications of the findings are discussed.